Answer:
see below
Step-by-step explanation:
(x) = 7 - 2x
Let t(x) =0
0 = 7-2x
Subtract 7 from each side
-7 = -2x
Divide by -2
-7/-2 =-2x/-2
7/2 =x
h(x) = 4x + 2
Replace x with x+3
h(x+3) = 4(x+3) + 2
Distribute
= 4x+12 +2
=4x+14
don't quote me on this but I'm pretty sure it's H multiplication property of inequality
Answer:
3
Step-by-step explanation:
![\bf \textit{surface area of a cylinder}\\\\ SA=2\pi r(h+r)~~ \begin{cases} r=radius\\ h=height\\[-0.5em] \hrulefill\\ r=13.5\\ h=90 \end{cases}\implies SA=2\pi (13.5)(90+13.5) \\\\\\ SA=27\pi (103.5)\implies SA=2794.5\pi \implies SA\approx 8779.18](https://tex.z-dn.net/?f=%5Cbf%20%5Ctextit%7Bsurface%20area%20of%20a%20cylinder%7D%5C%5C%5C%5C%20SA%3D2%5Cpi%20r%28h%2Br%29~~%20%5Cbegin%7Bcases%7D%20r%3Dradius%5C%5C%20h%3Dheight%5C%5C%5B-0.5em%5D%20%5Chrulefill%5C%5C%20r%3D13.5%5C%5C%20h%3D90%20%5Cend%7Bcases%7D%5Cimplies%20SA%3D2%5Cpi%20%2813.5%29%2890%2B13.5%29%20%5C%5C%5C%5C%5C%5C%20SA%3D27%5Cpi%20%28103.5%29%5Cimplies%20SA%3D2794.5%5Cpi%20%5Cimplies%20SA%5Capprox%208779.18)
well, the last part will be with a calculator, but you can simply use the area in π terms.
Answer:
B. -1
Step-by-step explanation:
x^3-4x^2+2x+10=x^2-5x-3
We know it has 3 roots since it is a 3rd degree polynomial.
Two of the roots are (3+2i) and (3-2i)
Subtract x^2-5x-3 from both sides
x^3-4x^2+2x+10-(x^2-5x-3)=x^2-5x-3 -(x^2-5x-3)
Distribute the minus sign
x^3-4x^2+2x+10-x^2+5x+3=x^2-5x-3 -x^2+5x+3
x^3 -5x^2+7x +13 =0
Graphing this equation , we see that it crosses the x axis at x=-1
That covers the three roots, 1 real and two complex